Peran BPBD kota Semarang dalam penyediaan pelayanan korban bencana bagi penyandang disabilitas - Dawud, Muhammad (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
The purpose of writing a paper on the role of the government (BPBD) in providing disaster victim services for people with disabilities is to change the mindset of society that disabilities are one of the main vulnerable groups to be saved when a disaster occurs. BPBD needs to work together with related parties, including organizations of people with disabilities. , to map and identify people with disabilities in their area. This is important to ensure that emergency services can be tailored to individual needs. It is an important role for BPBD to involve the wider community in disaster planning, including people with disabilities and their families. This can help understand specific needs and adapt emergency response plans. BPBD can play a role in designing and building disability-friendly infrastructure in its area. This includes accessible evacuation routes, public facilities that can be used by all, and providing information in a format that is accessible to everyone. The benefits of holding training with people with disabilities will have a direct impact on improving social quality in society and have a good impact on Public Services based on real conditions in the field (evidence based), tolerance for disabilities for a peaceful society, as well as increasing the readiness of the community and people with disabilities in facing disasters. The role of this service will certainly encourage the implementation of disaster response character building by prioritizing vulnerable groups which is generally the benchmark in Indonesia, especially the implementation of the provision of public facilities for groups of people with disabilities which is currently being planned and implemented. Apart from that, it is believed that the implementation of this service should also encourage investors to continue investing in the peaceful development of this country, safe from all disasters that occur. Keywords: The Role of the Government (BPBD) in Disaster Victim Services for the Disabled.